Overall agreement between eGFR estimates obtained with the CKD- EPI, MDRD and CG formulae in patients with advanced HIV diseases - Vu, Quoc Dat; Nguyen, Dinh Hong Phuc; Ba, Dinh Thang (Tạp chí Y Dược Huế, 2022)
Background: Traditional CKD risk factors as well as HIV-related factors are major determinants of the prevalence of renal diseases among HIV patients. Few equations have been used in clinical practice for calculating creatinine clearance, however, the accuracy of these formulae in HIV patients has been different. Our goal was to evaluate the reliability of all three equations (Chronic Kidney Disease Epidemiology Collaboration, Modification of Diet in Renal Disease, and Cockcroft-Gault) to estimate GFR in HIV-infected patients. Materials and method: We conduct a retrospective, observational cohort study of patients with HIV infection who are first time in care at selected HIV OPCs in Vietnam. Results: In 1108 patients eligible for analysis, a major patient was in HIV clinical stage 3 and 4 with a median age of 36, and median serum creatinine of 0.89 mg/dL. eGFR calculated by CG equation was lower than CKD-EPI formulae in overall except overweight patients (p<0.05, paired t-test) while the similar results were observed in both CKD-EPI and MRDR (p=0.144, paired t-test). Conclusion: There was a substantial agreement between CKD-EPI and MDRD eGFR, agreement percentage of 90.1 and MDRD was reliable as CKD-EPI to calculate eGFR in the HIV population.